Relationship between therapeutic alliance and deep abdominal muscle recruitment in nonspecific low back pain sufferers - Paulo Roberto Carvalho do Nascimento; Paulo Henrique Ferreira; Fábio Mícolis de Azevedo; Rúben de Faria Negrão Filho (Universidade de São Paulo, 2014)
Chronic low back pain is a difficult condition to be treated. As some patients respond positively to treatment and others do not present any improvements, one can think there are others conditional factors that need to be elucidated. By means of this study, we sought to investigate the association between the occurrence of the formation of a positive relationship between patient and therapist, assessed by the therapeutic alliance inventory, and the adequate recruitment of the deep abdominal muscles, as well as to verify the effect of a protocol intervention based on motor control exercises on levels of pain and disability. The recruitment of the transverse abdominal and internal oblique muscles was examined by ultrasound imaging in 12 subjects with nonspecific chronic low back pain before and after implementation of a protocol for motor control exercises, with subsequent application of the therapeutic alliance inventory questionnaire. No association was found between the level of therapist/patient alliance and muscle recruitment. The proposed protocol was effective in reducing the levels of pain and disability; however, recruitment of transverse abdominal and internal oblique muscles showed no significant changes in the end of the intervention. Based on these findings, we verified that the therapeutic alliance has no association with muscle recruitment in the short term. However, although there were no changes in muscle recruitment after the intervention program, the level of pain and disability was reduced.